Is the high proportion of caesarean sections justified? Approaching this world trend - Alejandro Antonio Bautista-Charry; Ariel Iván Ruiz-Parra (Federación Colombiana de Obstetricia y Ginecología, 2014)
From our vantage point in the front lines, we have witnessed the speed at which our specialty has been moving towards the future. Several years ago, as we started our training in obstetrics, we came to Instituto Materno Infantil, an institution with a long history, long-standing experience and a path that offered hope for a professional career faced with rapid transformations driven by technological breakthroughs. The practice at the time was that of great obstetrical manoeuvres, semiological examination, and difficult case discussions. Maternal mortality back then was close to 222 deaths for every 100,000 live births (1), as a result of a high frequency of eclampsia and associated neurological morbidity, and also complications of abortions performed in unsafe conditions. However, we had dreams of saving lives and we were there to see the birth of perinatology, a door opener to the foetus and neonate as patients in their own right. Perinatology looked into foetal wellbeing and moved steadily towards foetal surgery. Thus, perinatal medicine joined genetic engineering in its quest to arrive at the perfect human clone.